Anzac Day media representations of women in Perth 1960-2012 - Mayes, R.; Seal, Graham (Black Swan Press, 2014)
There is a substantial body of historical scholarly work which engages with women and war. Less attention, however, has been given to the representation of women as part of Anzac Day practice and mythology. This chapter begins to address this gap through examination of the ways in which women’s participation in successive Anzac Days in Perth from 1960 through to 2010 is represented in the media. Despite the remarkable growth in popularity of the day, especially the dawn service as a popular and official spectacle of nation, there is an ongoing marginalisation, if not silencing, of the diversity of women’s experiences of and contributions to Anzac.